Evaluation of alcohol consumption motivation: psychometric properties of the Alcohol Consumption Motivation Inventory by V.Yu. Zavyalov - A. V. Trusova; A. A. Berezina; A. N. Gvozdetckii; S. G. Klimanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The alcohol consumption motivation inventory (ACM) was developed by V.Yu. Zavyalov. Now it is a widespread psychometric tool in research and clinical practice for the evaluation of alcohol consumption motivation in Russian-speaking patients with alcohol use disorders. The aim of the study is to analyze the psychometric properties of the ACM inventory. Results show that the factor structure of the ACM inventory significantly differs from the one stated in the original. The results of the statistical analysis allowed three significant clusters. Cluster A was composed of the scales of the conditioned triad—traditional, submissive, and pseudo-cultural motives. This cluster also partially included hedonistic motives and self-harm motives. Cluster B was composed of scales of personal and pathological triads—withdrawal, ataractic and hyperactivational motives. Hedonistic motives and addictive motives were also partially included. Cluster B included self-harm motives and hangover (addictive) motives. According to the data obtained, the ACM inventory cannot measure an alcohol consumption motivation in the way of the original method. Future work on the modification of the ACM inventory should be based on the results obtained recently in neurophysiological and clinicalpsychopharmacological studies in the field of motivation for alcohol consumption, and includes the revision of the items of the questionnaire, a statistically substantiated gradation of levels for assessing the effectiveness of the motives for alcohol use, and the validation of the version of the ACM questionnaire in women sample.